(untitled) (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2025)
Some of the people on the island of Java who still carry out the rituals and concept of Manunggaling Kawula Gusti are the Kejawen people. Kejawen is a Javanese spiritual belief that contains traditions, rituals, as well as art and culture. The Javanese tribe is one of the tribes in Indonesia that has very strong local beliefs in the archipelago so that it has developed and become the soul of its people’s lives. In Javanese society, traditions and rituals certainly cannot be put aside because they have become part of their lives in believing in the existence of God and all its manifestations. The island of Java already has unique Indonesian beliefs and not religions originating from abroad. This also causes rituals and traditions to exist in Javanese society because of alcuturation. The concept of Manunggaling Kawula Gusti is the core of Wirid Hidayat Jati’s teachings which has the ideals of human life that humans must achieve, namely gaining an appreciation of unity with God through the path of samadhi. There are certain types and procedures, actors, facilities, times and places for doing Samadhi so that you can be suwung and Manunggaling Kawula Gusti. Through the success of Yoga Samadhi, humans can recognize the True Teacher as a good life guide and can Manunggaling Kawula Gusti. The function of Yoga Samadhi in the Manunggaling Kawula Gusti Concept is as a religious, social and educational function